2013
DOI: 10.1039/c3an00110e
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive enhancement of latent fingerprints on stainless steel surfaces by electrochemiluminescence

Abstract: Visualization and detection of latent fingerprints (LFPs) on metal surfaces are of highly practical importance, e.g., in identifying gun cartridges. We report herein the visualization of LFPs on stainless steel surfaces by electrochemiluminescence (ECL). Since organic residues, such as fatty acids, in the fingerprint deposit make the underlying surface electrochemically inert or less active, an ECL reaction occurs only on the metal portions untouched by the fingertip, hence generating a negative image of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Xu et al [29] have also proposed a technique for the visual enhancement of sebaceous latent fingermarks by electrochemiluminescence (ECL) which gave a satisfactory visual contrast. In addition to this, scanning electrochemical microscopy (SECM) [30], scanning Kelvin microprobe [31,32] and electrostatic deposition [24,25] techniques have also been reported to visualise identifiable latent fingermarks on metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [29] have also proposed a technique for the visual enhancement of sebaceous latent fingermarks by electrochemiluminescence (ECL) which gave a satisfactory visual contrast. In addition to this, scanning electrochemical microscopy (SECM) [30], scanning Kelvin microprobe [31,32] and electrostatic deposition [24,25] techniques have also been reported to visualise identifiable latent fingermarks on metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group developed an electrochemiluminescence (ECL) imaging method for visualizing LFPs by the spatially selective control of the location of ECL generation (Figure 1), using Ru(bpy) 3 2 [46] or rubrene [47] as the ECL luminophore. This method is particularly useful in visualizing LFPs on metal surfaces, e.g., stainless steel [48], that are often found in felony cases. Recently, Tan et al [49] demonstrated the visualization of oily LFPs and in situ detection of TNT in fingerprints by using an ECL-based image-contrast technology on the surface of porous silicon.…”
Section: Electrochemical Techniquesmentioning
confidence: 99%
“…In electrochemiluminescence, the light 45 emitting species are formed near the electrode surface which offers approach for imaging electrochemical or biosensing events. 330 In their study, they produced a negative image of fingerprint using electrochemiluminescence. Fig.…”
Section: Other Anti-counterfeiting Applications Based On Electroluminmentioning
confidence: 99%